2002
DOI: 10.1002/cyto.10150
|View full text |Cite
|
Sign up to set email alerts
|

Detection of in situ activation of transglutaminase during apoptosis: Correlation with the cell cycle phase by multiparameter flow and laser scanning cytometry

Abstract: Background:One of the hallmarks of apoptosis is activation of tissue transglutaminase (Tgase; also called transglutaminase type 2 [TGase 2]). Its activation causes cross-linking of cytoplasmic proteins, making them insoluble and presumably less immunogenic. Several biochemical and cytochemical methods to detect activity of TGase 2 exist, but none has been adapted for multiparameter flow or image cytometry. Methods: Apoptosis of HL-60 or U-937 leukemic cells was induced by camptothecin, tumor necrosis factor ␣,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…5A). Resistance of apoptotic cells to the nonionic detergent Triton X-100 was reported to correlate with activity of TG2, which mediates protein cross-linking (39). During apoptosis, the proportion of 7-AAD + cells and the level of 3B9 binding to these cells were comparable irrespective of Triton X-100 treatment (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…5A). Resistance of apoptotic cells to the nonionic detergent Triton X-100 was reported to correlate with activity of TG2, which mediates protein cross-linking (39). During apoptosis, the proportion of 7-AAD + cells and the level of 3B9 binding to these cells were comparable irrespective of Triton X-100 treatment (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…TG2-mediated protein-protein cross-linking in apoptotic cells was investigated using a modification of a previously described method (39). Briefly, cells were resuspended at 1 Â 10 6 /mL in PBS containing 1% Triton X-100, 0.2 Ag/mL sulforhodamine-101, and 0.1 Amol/L SytoxGreen.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, 3B9 still bound EL4 cells killed with cytotoxic drugs after treatment with nonionic detergent, which suggested that La was cross-linked in dead cells (ref. 37; Fig. 1D).…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, this cytometer is more versatile and have been used in several scientific studies (35,40,41).…”
Section: Discussionmentioning
confidence: 99%